The Trend of Malaria Cases, Positivity Rate, and Determinant Factors in the Amhara Regional State, Ethiopia: A Mixed Method - Chalachew Yenew; Sileshi Mulatu; Asaye Alamneh (Case Reports in Infectious Diseases)
Objectives. The objectives of this study were to evaluate the trend of malaria cases and test positivity rate and explore determinant factors in the Amhara Regional State, Ethiopia. Methods. A mixed study design (retrospective record data review and case study) was employed among 67 malaria officers from all zones in the region by using proportional allocation and the 1995 to 2020 malaria document review. 1995 to 2020 trend analysis was conducted using RStudio-1.2.5033. Vignette Focus Group Discussions (FGDs) were used to dig the possible factors for malaria case buildup using the purposive sampling technique, and a qualitative content analysis was used. Results. The overall mean test positivity rate (TPR) was 21.9%, and about 80% of the land of the region was malarious, and 68% of the population was at risk of malaria in the study area from the data records of 1995 to 2020. The year 2012 to 2016 had the peak confirmed malaria cases, while the year 2016 to 2018 dramatically reduced followed by an increase in 2019/2020. The vignette FGDs identified that poor performance on Larval Source Management (LSM) and net utilization, no stock of some antimalarial medicine and supply, quality of malaria diagnosis services, the low commitment of leaders, and climatic anomalies facilitated surge of the disease in 2019/2020. No real accountability at all levels, low coverage of targeted vector control interventions, resource constraint, data quality and use for informed decision making, security issues and Internally Displaced Population (IDP) in various parts of the country, and the COVID-19 pandemic were the possible causes for case buildup. Conclusions. This result revealed that the malaria incidence rate showed a remarkable decline. However, the average TPR was 21.9%. Hence, it provided the ongoing feedback, mass fever test and treatment, training to health professionals, and ongoing supportive supervision (SS) and mentorship, improved net utilization and indoor residual spraying (IRS) operation and close follow-up and conducted sensitization workshop, spot messages were transferred through mass media, and temporary case treatment and prevention centers at farm sites established may surpass the threshold of malaria.